2016
DOI: 10.1007/s00167-016-4222-y
|View full text |Cite
|
Sign up to set email alerts
|

Does meniscus removal affect ACL-deficient knee laxity? An in vivo study

Abstract: The present study shows that meniscal defects significantly affect the kinematics of an ACL-deficient knee in terms of anterior tibial translation under static and dynamic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…They also contribute mechanical stability of the knee along with cruciate ligaments specially rotary stability giving additional gliding function to the hinge type of knee joint [9] . Meniscectomy has bad influence on joint alignment, load distribution and anterior instablilty [3,4,5] . Medial meniscectomy increases tibio femoral contact stresses by 100% whereas lateral meniscectomy increases contact stresses by 200% to 300%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also contribute mechanical stability of the knee along with cruciate ligaments specially rotary stability giving additional gliding function to the hinge type of knee joint [9] . Meniscectomy has bad influence on joint alignment, load distribution and anterior instablilty [3,4,5] . Medial meniscectomy increases tibio femoral contact stresses by 100% whereas lateral meniscectomy increases contact stresses by 200% to 300%.…”
Section: Resultsmentioning
confidence: 99%
“…Follow up as long as 40 years after medial meniscectomy has shown reduced femoro tibial angle leading to varus malalignment and lower flexion range of the knee [3] . Lorbach et al has shown that medial meniscectomy increases anterior tibial translation in ACL deficient knees by significant amount by Lorbach et al [4,5] Total lateral meniscectomy or its untreated root tear is also associated with increase posterolateral rotary instability postoperatively due to its anatomical proximity to popliteus tendon and posterolateral capsule [6] . Meniscus repair has higher healing potential.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of medial meniscus removal on AP laxity, several cadaveric studies have reported results that are consistent with those of the present study. 15,22,36 Lorbach et al, 14 in an experimental setting of 18 human knee specimens with transected ACL, showed a significant increase of anterior tibial translation after partial medial meniscectomy with respect to the isolated ACL injury using a robotic testing system. Despite different settings and instruments, the values of 13.6 mm for isolated ACL sectioning and 15.4 mm for ACL and medial meniscectomy during the Lachman maneuver at 30° are consistent with the values of 11.1 and 15.8 mm, respectively, reported in the 2 groups of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of resected meniscal tissue should not be overlooked, as subtotal meniscectomies due to bucket-handle tears have been proved to produce greater laxity compared with partial meniscectomies of the posterior horn. 36 Despite the amount of meniscectomy, Seon et al 26 concluded that the effect of medial meniscectomy “was larger at higher flexion angle than lower flexion angle” after ACL reconstruction. This insight from their cadaveric study is confirmed by the data of the present in vivo evaluation, where in fact a significantly greater laxity was found only at 90° of flexion and, conversely, a greater laxity reduction after ACL reconstruction was found at 30°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation